The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18203/2319-2003.ijbcp20185174
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions associated with first line anti-tubercular drugs, their prevalence and causality assessment in patients on Directly Observed Treatment Short-course (DOTS) in a tertiary care hospital

Abstract: Background: Treatment of tuberculosis involves giving multiple drugs to the patient which is done to prevent development of resistance besides targeting all bacterial sub-populations. The objective of the present study was to find out the adverse drug reactions (ADRs) of the first line anti-tubercular drugs and to calculate prevalence and causality of these drugs.Methods: The study was conducted by the Department of Pharmacology, Government Medical College, Srinagar in association with the department of Chest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, it breaks down the entero-hepatic circulation of biliary acids on liver metabolic processes (Pongcharoen & Fleischer Jr, 2016 ). Previous studies have also commonly reported this side effect (Fei, Zainal, & Ali, 2018 ; Nazir, Farhat, Adil, & Asrafv, 2019 ; Sinha, Marak, & Singh, 2013 ).…”
Section: Discussionmentioning
confidence: 71%
“…However, it breaks down the entero-hepatic circulation of biliary acids on liver metabolic processes (Pongcharoen & Fleischer Jr, 2016 ). Previous studies have also commonly reported this side effect (Fei, Zainal, & Ali, 2018 ; Nazir, Farhat, Adil, & Asrafv, 2019 ; Sinha, Marak, & Singh, 2013 ).…”
Section: Discussionmentioning
confidence: 71%